WEB BASED MANAGEMENT SYSTEM FOR ENACTUS MALAYSIA NATIONAL CUP (E-EMNC) - Seah Choon Sen; Hanayanti Hafit,; Shahreen Kasim; Mohd Farhan Md Fudzee; Azizul Azhar Ramli; Hairulnizam Mahdin (Acta Informatica Malaysia, 2017)
Web Based Management System of Enactus Malaysia National Cup (E-EMNC) is event management system that specially designed for the uses of Enactus Malaysia National Cup. Without a proper event management system, Enactus Malaysia National Cup cannot be perfect enough due to several outburst issues such as miss update of payment, long queue at registration counter, misunderstand of information and others. Thus, this event management system was developed to overcome most of the problem that occurs before, during and after the events. Related objectives are stated to solve the problem. System Development Life Cycle Waterfall model is used as the methodology to develop this system. This system is developed by using PHP as server-side scripting and Bootstrap as front end framework. The prototype of the system was considered success because it could navigate student leader to complete submit the report by shown the flow of system. This system is expected to lighten the burden of event committees and educated team leader on filing document through internet.